Estudo comparativo entre ileostomia e colostomia na descompressão temporária de anastomose colorretal: Revisão sistemática da literatura e metanálise - Güenaga, Katia Ferreira [UNIFESP] (2006)
Purpose: To assess the evidence in the use of loop ileostomy compared with loop transverse colostomy for temporary decompression of colorectal anastomosis. Method: A systematic review of the literature and metanalysis with randomized controlled trials accessed from MEDLINE, EMBASE, LILACS, COCHRANE CONTROLLED TRIALS DATABASE. The outcomes remarked were: mortality; wound infection; time of formation of stoma; time of closure of stoma; time interval between formation and closure of stoma; stoma prolapse; stoma retraction; paraostomal hernia; paraostomal fistula; stenosis; necrosis; skin irritation; ileus; bowel leakage; reoperation; leakage from the appliance; number of appliances changed required per day; alterations in diet; need of medication; odour from the stoma; psychosocial sequelae; length of hospital stay; colorectal anastomotic dehiscence; incisional hernia; postoperative bowel obstruction. For data analysis the relative risk and risk difference were used with corresponding 95% confidence interval. Statistical heterogeneity in the results of the metanalysis was assessed by calculating a test of heterogeneity. The software Review Manager 4.2.8 (Cochrane Collaboration) was utilized for the data gathered and the statistical analysis. Results: Five trials were included with 334 patients: 168 to loop ileostomy group and 166 to loop transverse colostomy group. The continuous outcomes could not be measured because of the lack of the data. The outcomes stoma prolapse had statistical significant difference: p<0.00001, but with statistical heterogeneity, p=0,001, I²=81.2%. Sensitive analysis was applied excluding the trial that included emergencies surgeries, the result had a difference: p=0.02, and test for heterogeneity: p=0.68, I²=0%. Conclusion: The best available evidence for the use of loop ileostomy or loop colostomy when a decompression of colorectal anastomosis is recommended is yet come. The less incidence of stoma prolapse in the ileostomy group indicates this proceeding as a method of temporary decompression of colorectal anastomosis, when compared with colostomy.